Artificial Intelligence Integration in Secondary Education: A Systematic Review - Guerra Olivella, Rafael (2026)
The purpose of this study was to examine pedagogical approaches that secondary schools employed from 2021 to 2024 to include generative artificial intelligence (GenAI), as well as determine significant limitations. The PRISMA principles were used to perform a systematic review that included 43 articles from scholarly journals that focused on research and experiences using AI technologies. Automated tutoring, comprehensive curricular units, multidisciplinary projects, and individual activities were the four main implementation alternatives that were identified. These strategies vary in pedagogical depth and are shaped by factors including teacher education, infrastructure, and institutional context. Notable findings indicate that methods with robust GenAI integrations (such as interdisciplinary projects, curricular units, and automated tutoring) significantly enhance cognitive and metacognitive abilities, including argumentation, sophisticated problem-solving, and reflective decision-making. Conversely, solo activities yield more surface effects, exemplified by expedited job completion devoid of profound critical engagement. The principal obstacles to successful GenAI integration in secondary education include insufficient teacher preparation, inequities in access to technological resources, ethical concerns, and cultural resistance to change. Findings underscore the necessity of conducting context-specific empirical research to guide future decisions on the pedagogical, critical, and equitable application of digital technology in secondary education.